2021
DOI: 10.3390/cancers13194855
|View full text |Cite
|
Sign up to set email alerts
|

Heat Shock Protein 27, a Novel Downstream Target of Collagen Type XI alpha 1, Synergizes with Fatty Acid Oxidation to Confer Cisplatin Resistance in Ovarian Cancer Cells

Abstract: Collagen type XI alpha 1 (COL11A1) is a novel biomarker associated with cisplatin resistance in ovarian cancer. We have previously reported that COL11A1 activates Src-Akt signaling through the collagen receptors discoidin domain receptor 2 (DDR2) and integrin α1β1 to confer cisplatin resistance to ovarian cancer cells. To identify the potential signaling molecules downstream of COL11A1 signaling, we performed protein kinase arrays and identified heat shock protein 27 (HSP27) as a potential mediator of COL11A1-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
19
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(26 citation statements)
references
References 47 publications
(94 reference statements)
2
19
0
1
Order By: Relevance
“…An enrichment of acetylated histones H3 was found around the BIRC3 promoter (Figure 5B), which suggests that NF-κB-enhanced expression of BIRC3 may occur by promoting histone acetylation in ESCA, just like that in breast cancer [28]. Activated NF-κB and up-regulated IAPs (BIRC2 and BIRC3) in ovarian cancer cells might mediate chemotherapy resistance [29].…”
Section: Discussionmentioning
confidence: 92%
“…An enrichment of acetylated histones H3 was found around the BIRC3 promoter (Figure 5B), which suggests that NF-κB-enhanced expression of BIRC3 may occur by promoting histone acetylation in ESCA, just like that in breast cancer [28]. Activated NF-κB and up-regulated IAPs (BIRC2 and BIRC3) in ovarian cancer cells might mediate chemotherapy resistance [29].…”
Section: Discussionmentioning
confidence: 92%
“…Acylcarnitines are generated via esterification of fatty acids and shuttle lipids into the mitochondrial matrix for β-oxidation ( 39 ). Reduced acylcarnitine levels imply impaired fatty acid oxidation and mitochondrial dysfunction, which are implicated in OC ( 40 , 41 ). Additionally, an association was observed between tetradecanoylcarnitine and a diminished risk of HGSOC.…”
Section: Discussionmentioning
confidence: 99%
“…Increasing reports demonstrated that FAO contributed to chemoresistance in gastric [ 28 ], breast [ 29 ], ovarian [ 30 ], and hepatocellular carcinomas [ 31 ]. Pharmacological inhibition of FAO sensitized leukemia cells to apoptosis [ 32 ], and synergetic of FAO inhibitors with Ara-C eradicated bone marrow resident chemoresistance AML cells [ 33 ].…”
Section: Discussionmentioning
confidence: 99%